Hubungan Pola Makanan Dan Tingkat Pengetahuan Ibu Terhadap Diare Pada Balita - Nisa Kartika Ningsih; Indria Apriani; Silvia Mariana; Rosa Riya (Lontara Journal of Health Science and Technology, 2023)
In Indonesia, the infant mortality rate caused by diarrhea reaches 1.5 million per year. The greatest incidence occurs in the first 2 years of life and decreases as the child grows. The purpose of this study was to find out the relationship between food patterns and mother's level of knowledge about diarrhea in toddlers. This study used a random sampling design with a population of 39 samples. The research design in this study was by filling out a questionnaire. The sampling technique is 39 mothers who have toddlers. Data analysis used the chi-square test. The results of this study were obtained from the results of data analysis using chi-square indicating that there are factors for diarrhea. p-value 0.011 (<0.05) which means that there is a relationship between mother's knowledge and diarrhea in toddlers, p-value 0.044 (<0.05) which means that there is a relationship between diet and diarrhea in toddlers